Evaluation of the neurotoxic activity of ethylene glycol ethers – in vitro and in vivo research - Pomierny, Bartosz Sebastian (2015)
Ethylene glycol ethers (EGEs) due to their favorable physicochemical properties are widely used as ingredients in many household preparations, paints, coatings and medical products. Because the exposure to EGEs is high and, so far, there were no data concerning their influence on the mammalian cells of the central nervous system (CNS), thus the aim of this study was to evaluate, in the in vivo and in vitro model, potential, neurotoxic action of these compounds. In the in vivo model, we evaluated the influence of 4-week administration of 2-ethoxyethanol, 2-butoxyethanol and 2-phenoxyethanol (PHE), on the markers of oxidative stress and apoptosis in the rats frontal cortex and hippocampus. In in vitro studies, on SH-SY5Y cells, we determined the impact of EGEs and their metabolites on cells viability, level of released lactate dehydrogenase (necrosis), caspase-3 activity, and the mitochondrial membrane potential (apoptosis). To determine the intracellular mechanism of the toxicity of PHE and its metabolite, we investigated the influence of specific inhibitors of protein kinases on cytotoxic and proapoptotic effects of EGE and its metabolite. For this research we have chosen kinase inhibitors such as inhibitors of GSK-3β, p38-MAPK, JNK-MAPK, PLC.In vivo results of this study suggest that EGEs with lipophilic properties exert toxic influence on the CNS cells through raised oxidative stress and activated apoptosis.In vitro results indicate that the cytotoxic and proapoptotic effect of EGEs and metabolites may stem from their impact on many intracellular signal transduction pathways, mainly GSK3β, p38, JNK.We can conclude that long-term exposure to EGEs might be one of the reasons for the raised prevalence to neurodegenerative diseases.
Keywords: ethylene glycol ethers; alkoxyacetic acids; neurotoxicity; apoptosis; oxidative stress

Acute kidney injury in course Hantavirus infection – analysis diseases from the Podkarpacki region - Bentkowski, Wacław (2015)
Viral haemorrhagic fevers are zoonoses infections. They differ in clinical course, ways of infection, disease symptoms, and their common feature is hemorrhages to the internal organs and the skin. In Europe, there are mainly two Hantvirus serotypes: Puumala serotype which causes a mild form of haemorrhagic fever called epidemic nephropathy and Dobrava serotype which causes hemorrhagic fever with renal syndrome (HFRS).In the Podkarpacki region during 2007-2012 Hantavirus infection disease was found in 38 patients; serotype Dobrava 50% and serotype Puumala 50%. The aim of the study was to assess what percentage of Hantavirus-infected patients have kidney damage, what were the predominant symptoms from the urinary tract, what was the duration of acute kidney injury (AKI), and the evaluation of the consequences of Hantavirus infection. Dominant signs of Hantavirus infection are flu-like symptoms with a high temperature, discomfort on the part of the digestive system, volemia disorders, low levels of platelets, elevated serum creatinine, urea nitrogen and CRP. AKI occurred in 75% of patients and lasted about of 9 days. 5 patients requiring hemodialysis. A complete remission of renal function was observed in 68% of patients and partial in 32%. AKI of Hantavirus infection does not result in permanent damage of the kidney.
Keywords: Puumala virus; Dobrava virus; haemorrhagic fever with renal syndrome; acute kidney injury (AKI); Podkarpacki region